Multifaktorial Keluarga Beresiko Stunting di Kalimantan Tengah - linda puji astutik; Yena Wineini Migang (PT Nuansa Fajar Cemerlang, 2025)
Families at risk of stunting are one of the 5 (five) priority activities in the National Action Plan for theAcceleration of Stunting Reduction. The purpose of this study is to analyze the multifactorial families at riskof stunting in Central Kalimantan. type of analytical research with Cross Sectional study design. Datacollection uses secondary data, namely the 2023 Central Kalimantan Province PK-23 update report. Thepopulation in this study is the target of PK-23, namely couples of childbearing age, pregnant women, familieswith children aged 0-23 months and families with children aged 24-59 months. The sampling technique useda total sampling of 379,044 with exclusion criteria being incomplete data and categories of measurementresults that were not in accordance with the research variables. The independent variables in this study were families with baduta, families with toddlers, families with pregnant puse, unsuitable water sources, unsuitablelatrines, pus too young, pus too old, pus too close, pus too much, not modern family planning participants. The bound variable is families at risk of stunting. Univariate data analysis was carried out to see the distribution of each variable. Chi-square test From the results of the statistical test, it is known that the multifactors related to families at risk of stunting are families with Baduta (p-value= 0.001), families with toddlers (p-value= 0.001), Families with Pregnant PUS (p-value= 0.001), Unsuitable Water Sources (p-value= 0.000), Unsuitable Toilet Ownership (p-value= 0.000), PUS Too Young (p-value= 0.001), PUS Too Old (pvalue= 0.000), Too Much PUS (p-value= 0.000), and Non-Modern Family Planning Participants (p-value=0.000). Suggestions to stakeholders of the stunting reduction acceleration program can evaluate the effectiveness of the program and obstacles in the field